PKM Pelatihan Riset dari Rumah untuk Percepatan Studi Mahasiswa - Wirawan Setialaksana; Abdal, Nurul Mukhlisah; Amir, Johar; Jamaluddin; Baso, Fadhlirrahman (TEKNOVOKASI : Jurnal Pengabdian Masyarakat, 2023)
The rapid development of higher education in Indonesia has led students to actively contribute to societal development through research, particularly in quantitative research. However, students face challenges, such as slow research progress and resource constraints. This article proposes an innovative solution by harnessing Information and Communication Technology (ICT) to support student research. The utilization of online applications and platforms, especially in the context of quantitative research, is expected to expedite research progress and provide greater flexibility. Support from higher education institutions and the government, including adequate infrastructure and training, is essential to ensure the sustainability of this solution. Additionally, a holistic approach emphasizing digital literacy, research ethics, and collaboration among students can enhance research quality. The article also presents the implementation method of quantitative research training using the JAMOVI application, followed by a follow-up plan to ensure sustained understanding and practical application. The results show that remote research training has a positive impact, enabling students to maximize the potential of technology for research advancement and scientific contributions. The program provides in-depth insights into the concepts of quantitative research, the installation and use of the JAMOVI application, and reinforcement through discussions and case studies. In conclusion, the implementation of remote research in students forms a solid foundation for advancing higher education in Indonesia, and follow-up measures are necessary to maintain sustainability and enhance program effectiveness.